Patellofemoral kinematics and TT-TG distances in adolescent females with patellofemoral pain - Carlson, Victor R. (Am J Sports Med, 2016)
BACKGROUND: Patellofemoral pain is a prevalent disorder among female adolescents. Overuse is frequently cited as the etiology of pain for this population. What is currently unclear, however, is if the patella demonstrates abnormal tracking patterns relative to the femoral trochlear groove in adolescent females with patellofemoral pain. PURPOSE: The aim of this case-control study is to determine if abnormal patellar tracking patterns are present in adolescent females with patellofemoral pain. The secondary aim is to identify if an increased distance between the tibial tuberosity and trochlear groove (TT_TG) is associated with the observed kinematic patterns. STUDY DESIGN: Case Control METHODS: Twenty female adolescent knees from 12 subjects with patellofemoral pain and 20 age-matched female knees from 13 healthy controls were recruited for this study. Patellofemoral kinematics (e.g., lateral patellar displacement) during a repetitive knee extension-flexion maneuver were quantified from dynamic cine-phase-contrast magnetic resonance imaging techniques. Static magnetic resonance images were used to determine the TT-TG distance. RESULTS: Relative to the control cohort, female adolescents with patellofemoral pain demonstrated significantly greater lateral displacement at 10° (3.2mm, p<0.001), 20° (2.3mm, p<0.001), and 30° (1.7mm, p=0.014) of knee flexion. A subgroup within this cohort (7 knees from 5 subjects) demonstrated extreme lateral maltracking >2 standard deviations beyond the average control. This subgroup also demonstrated a greater distance between the tibial tuberosity and trochlear grove relative to controls (Δ=4.2mm, p=0.001). CONCLUSIONS: This study demonstrates that abnormal patellar tracking patterns are present in adolescent females with patellofemoral pain. Since all subjects from both cohorts participated in impact sports, it appears that rigorous athletic training alone is inadequate to produce symptoms in this population. Rather, patellofemoral pain may derive from a combination of physical activity in the context of pathologic kinematics.